Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

JP7634182B2Active Publication Date: 2025-02-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021574040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2021-01-26
Publication Date
2025-02-21
Estimated Expiration
2041-01-26

Smart Images

  • Figure 0007634182000002
    Figure 0007634182000002
  • Figure 0007634182000003
    Figure 0007634182000003
  • Figure 0007634182000001
    Figure 0007634182000001
Patent Text Reader

Abstract

This positive electrode active substance for a non-aqueous electrolyte secondary battery contains a lithium-transition metal composite oxide which has a crystal structure belonging to the space group Fm-3m and is represented by the compositional formula LixMnyMaObFc (in the formula: M is at least one type of metal element excluding Mn; x+y+a=b+c=2; 1 < x ≤ 1.35; 0.4 ≤ y ≤ 0.9; 0 ≤ a ≤ 0.2; and 1.3 ≤ b ≤ 1.8). In addition, the lattice constant a of the lithium-transition metal composite oxide is 4.09-4.16.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the same.

Background Art

[0002] In non-aqueous electrolyte secondary batteries such as lithium-ion batteries, the positive electrode active material greatly affects battery performance such as input / output characteristics, capacity, and cycle characteristics. As the positive electrode active material, for example, NCM-based lithium transition metal composite oxides containing Ni, Co, and Mn are widely used. In recent years, as a next-generation positive electrode active material with high capacity, a Li-excess type material based on rock salt structure Li x Mn 1-x O2 has attracted attention.

[0003] For example, Patent Document 1 discloses a positive electrode active material containing a lithium transition metal composite oxide having a crystal structure belonging to the space group Fm-3m and represented by the composition formula Li 1+x Nb y Me z A p O2 (Me is a transition metal containing Fe and / or Mn, 0 < x < 1, 0 < y < 0.5, 0.25 ≦ z < 1, A is an element other than Nb and Me, 0 ≦ p ≦ 0.2, provided that Li 1+p Fe 1-q Nb q O2, excluding those where 0.15 < p ≦ 0.3 and 0 < q ≦ 0.3).

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

[0005] As described above, rock salt structure Li x Mn 1-xO2-based materials are expected to be high-capacity cathode active materials, but they have a wide voltage distribution (with various Li environments), and in reality, there is a large amount of unused capacity. Therefore, the high capacity as expected has not been achieved. The same is true for the cathode active material disclosed in Patent Document 1, and a breakthrough for high capacity is necessary.

[0006] The cathode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure has a crystal structure belonging to the space group Fm-3m, and the composition formula is Li x Mn y M a O b F c (wherein M is at least one metal element other than Mn, x + y + a = b + c = 2, 1 < x ≤ 1.35, 0.4 ≤ y ≤ 0.9, 0 ≤ a ≤ 0.2, 1.3 ≤ b ≤ 1.8), and includes a lithium transition metal composite oxide, and the lattice constant a of the lithium transition metal composite oxide is 4.09 to 4.16.

[0007] A non-aqueous electrolyte secondary battery according to one aspect of the present disclosure includes a cathode containing the above cathode active material, an anode, a separator interposed between the cathode and the anode, and a non-aqueous electrolyte.

[0008] According to the present disclosure, a high-capacity cathode active material can be provided. According to the cathode active material according to the present disclosure, a significant increase in the capacity of a non-aqueous electrolyte secondary battery can be achieved.

Brief Description of the Drawings

[0009] [Figure 1] FIG. 1 is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an embodiment. [Diagram 2] FIG. 2 is a diagram showing the relationship between the composition of a cathode active material and the lattice constant a as an example of an embodiment.

Modes for Carrying Out the Invention

[0010] As described above, Li of the rock salt structure x Mn 1-xSince O2-based materials have a large amount of capacity that cannot actually be used, non-aqueous electrolyte secondary batteries using such materials have not been able to achieve the expected high capacity. As a result of intensive research into how to increase the capacity of such materials, the present inventors have found that the battery capacity can be specifically improved by introducing a predetermined amount of fluoride ions and making the lattice constant a smaller than the value predicted from the composition or controlling it to the range of 4.09 to 4.16. Although the mechanism of increasing the capacity is not well understood, the technology disclosed herein can be a breakthrough that leads to the practical application of high-capacity next-generation positive electrode active materials.

[0011] In this specification, the numerical value in parentheses attached to the lattice constant a indicates an error to three decimal places. For example, 4.115(2) means that the lattice constant a is 4.113 to 4.117. The lattice constant a is determined using integrated powder X-ray analysis software PDXL attached to an X-ray diffraction apparatus manufactured by Rigaku Corporation, and the lattice constant a determined by PDXL is given a numerical value indicating such an error range.

[0012] Hereinafter, with reference to the drawings, an example of an embodiment of a positive electrode active material for a nonaqueous electrolyte secondary battery according to the present disclosure and a nonaqueous electrolyte secondary battery using the positive electrode active material will be described in detail. Note that it is initially assumed that the multiple embodiments and modified examples described below will be selectively combined.

[0013] In the following, a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical exterior can 16 with a bottom is exemplified, but the exterior can is not limited to a cylindrical exterior can, and may be, for example, a square exterior can (square battery) or a coin-shaped exterior can (coin battery), or may be an exterior body (laminated battery) made of a laminate sheet including a metal layer and a resin layer. The electrode body may also be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators between them.

[0014] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the nonaqueous electrolyte secondary battery 10 includes a wound electrode assembly 14, a nonaqueous electrolyte, and an exterior can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the exterior can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the exterior can 16 is referred to as the bottom.

[0015] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more of these are used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. For example, a lithium salt such as LiPF6 is used as the electrolyte salt. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte.

[0016] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0017] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.

[0018] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.

[0019] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0020] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.

[0021] [Positive electrode] The positive electrode 11 has a positive electrode core body and a positive electrode composite layer provided on the surface of the positive electrode core body. For the positive electrode core body, a foil of a metal stable within the potential range of the positive electrode 11 such as aluminum or an aluminum alloy, a film having such a metal disposed on the surface layer, etc. can be used. The positive electrode composite layer contains a positive electrode active material, a conductive material, and a binder, and is preferably provided on both sides of the positive electrode core body. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, a binder, etc. on the positive electrode core body, drying the coating film, and then compressing to form the positive electrode composite layer on both sides of the positive electrode core body.

[0022] Examples of the conductive material contained in the positive electrode composite layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode composite layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resin, acrylic resin, polyolefin resin, etc. These resins may be used in combination with a cellulose derivative such as carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0023] The positive electrode active material has a crystal structure belonging to the space group Fm-3m and contains a lithium transition metal composite oxide represented by the composition formula Li x Mn y M a O b F c (wherein M is at least one metal element other than Mn, x + y + a = b + c = 2, 1 < x ≤ 1.35, 0.4 ≤ y ≤ 0.9, 0 ≤ a ≤ 0.2, 1.3 ≤ b ≤ 1.8). The composite oxide is a Li-excess system material in which the molar ratio of Li to the transition metal exceeds 1. Also, a predetermined amount of fluoride ions (0.2 ≤ c ≤ 0.7) is introduced and a part of O is substituted by F.

[0024] In the positive electrode 11, a complex oxide other than the complex oxide (for example, a complex oxide that is not Li-excessive or a complex compound that does not contain fluoride ions) may be used in combination as a positive electrode active material, but the content of the complex oxide is preferably 50 mass% or more, and may be substantially 100 mass%. The composition of the complex oxide can be measured using an ICP emission spectrometer (iCAP6300 manufactured by Thermo Fisher Scientific).

[0025] The lithium transition metal complex oxide has a rock-salt type crystal structure belonging to the space group Fm-3m. The rock-salt type crystal structure belonging to the space group Fm-3m is usually an irregular structure in which lithium and transition metals are randomly arranged, but the complex oxide of this embodiment has a lattice constant a that is out of the lattice constant predicted from the composition, as described later, and the random arrangement may be ordered to some extent. The crystal structure of the complex oxide is identified from the X-ray diffraction pattern measured using a powder X-ray diffractometer (MiniFlex desktop X-ray diffractometer manufactured by Rigaku Corporation, X-ray source: CuKα).

[0026] Figure 2 shows the composition formula Li 1+x Mn 1-x-y M y O 2-2x F 2x The horizontal axis shows the relationship between the composition and the lattice constant a of a lithium transition metal composite oxide represented by the composition formula Li 1+x Mn 1-x-y M y O 2-2x F 2x 2, the vertical axis represents the lattice constant a, and the dashed line in FIG. 2 represents the lattice constant predicted from the composition (composition ratio of LiF and LiMnO2), and the black circle represents the lattice constant a of the lithium transition metal composite oxide of this embodiment.

[0027] The lithium transition metal composite oxide according to one embodiment of the present invention has the composition formula Li 1+x Mn 1-x-y M y O 2-2x F 2xIn this case, x satisfies 0 < x ≤ 0.35, preferably 0.1 ≤ x ≤ 0.35, and more preferably 0.1 ≤ x ≤ 0.3. As shown in FIG. 2, the lattice constant a of the lithium transition metal composite oxide is smaller than the lattice constant predicted from the composition. When the crystal structure belongs to the space group Fm-3m, has the above composition, and satisfies the condition of the lattice constant a, the capacity of the composite oxide is specifically improved.

[0028] In one aspect of the embodiment, the lattice constant a of the lithium transition metal composite oxide is 4.09 to 4.16, preferably 4.10 to 4.15, and more preferably 4.11 to 4.14. The composition formula is Li 1+x Mn 1-x-y M y O 2-2x F 2x In the lithium transition metal composite oxide represented by, for example, when 0.1 ≤ x ≤ 0.35 and the lattice constant a is 4.09 to 4.16, the effect of increasing the capacity becomes more remarkable.

[0029] As described above, the lithium transition metal composite oxide according to one aspect of the embodiment may contain a metal element other than Li and Mn. For example, in the above composition formula Li x Mn y M a O b F c Examples of the metal element M in include at least one selected from Ni, Co, Fe, Al, Sn, Cu, Nb, Mo, Bi, Ti, V, Cr, Y, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, Ta, W, La, Ce, Pr, Sm, Eu, Dy, Er. Among them, at least one selected from Ni, Sn, Mo, Ti, W, Zn, Al is preferable.

[0030] The above composition formula Li x Mn y M a O b F cThe composition ratio x of Li is 1 < x ≤ 1.35, preferably 1.1 ≤ x ≤ 1.35, more preferably 1.1 ≤ x ≤ 1.3. In this case, the effect of increasing the capacity becomes more prominent. Also, the composition ratio b of O is 1.3 ≤ b ≤ 1.8, preferably 1.35 ≤ b ≤ 1.8. That is, the composition ratio c of F is 0.2 ≤ c ≤ 0.7, preferably 0.2 ≤ c ≤ 0.65. The ratio (N F / N O ) of the number of moles of F to the number of moles of O is, for example, 0.1 to 0.6, preferably 0.5 or less.

[0031] The above lithium transition metal composite oxide can be synthesized, for example, by using lithium fluoride (LiF) and lithium manganate (LiMnO2) as raw materials and performing a mixing treatment with a planetary ball mill in an inert gas atmosphere such as Ar. LiO2 and Mn2O3 may be used as raw materials. Also, instead of a planetary ball mill, a mixer capable of applying the same stirring shear force to the powder may be used, and the powder may be heated during the mixing process. The composition, lattice constant a, etc. of the composite oxide can be adjusted to the desired range, for example, by changing the mixing ratio of LiF and LiMnO2, the mixing conditions (rotation speed, treatment time, treatment temperature, etc.).

[0032] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite material layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal stable within the potential range of the negative electrode 12 such as copper, a film having the metal disposed on the surface layer, etc. can be used. The negative electrode composite material layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core. The negative electrode 12 can be produced, for example, by applying a negative electrode composite material slurry containing a negative electrode active material, a conductive material, a binder, etc. to the surface of the negative electrode core, drying the coating film, and then compressing it to form the negative electrode composite material layer on both sides of the negative electrode core.

[0033] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.

[0034] As the conductive material contained in the negative electrode mixture layer, carbon materials such as carbon black, acetylene black, ketjen black, and graphite can be used, as in the case of the positive electrode 11. As the binder contained in the negative electrode mixture layer, fluororesin, PAN, polyimide, acrylic resin, polyolefin, and the like can be used, as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), and the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.

[0035] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene, polypropylene, a copolymer of ethylene and α-olefin, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer containing inorganic particles, or a heat-resistant layer made of a highly heat-resistant resin such as an aramid resin, a polyimide, or a polyamideimide may be formed on the surface of the separator 13.

[0036] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0037] <Example 1> [Synthesis of positive electrode active material] Lithium fluoride (LiF) and lithium manganese oxide (LiMnO2) were mixed in a predetermined mass ratio. The mixed powder was placed in a planetary ball mill (Fritsch Premium-Line P7, rotation speed: 600 rpm, container: 45 mL, ball: Zr ball of φ3 mm) and treated in an Ar atmosphere at room temperature for 35 hours (35 cycles of 1 hour operation followed by 10 minutes of rest) to obtain a lithium manganese oxide having the composition formula Li 1.196 Mn 0.804 O 1.797 F 0.203 The lithium transition metal composite oxide represented by Got The X-ray diffraction pattern of the obtained composite oxide was measured and analyzed by the above method, and it was found that the obtained composite oxide had a crystal structure belonging to the space group Fm-3m and a lattice constant a of 4.135(2).

[0038] [Preparation of positive electrode] The obtained positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a solid content mass ratio of 7:2:1, and a positive electrode mixture slurry was prepared using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. Next, the positive electrode mixture slurry was applied onto a positive electrode core made of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to obtain a positive electrode.

[0039] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a predetermined volume ratio. LiPF6 was added to the mixed solvent to obtain a non-aqueous electrolyte.

[0040] [Preparation of test cell] The positive electrode and the negative electrode made of lithium metal foil were arranged opposite each other with a separator interposed therebetween to form an electrode assembly, which was then housed in a coin-shaped outer can. The nonaqueous electrolyte was poured into the outer can, and the outer can was then sealed to obtain a coin-shaped test cell (nonaqueous electrolyte secondary battery).

[0041] The initial discharge capacity of the test cell was evaluated by the following method, and the evaluation results are shown in Table 1 together with the composition and lattice constant a of the positive electrode active material.

[0042] [Evaluation of initial discharge capacity] The test cell was CC-charged at a constant current of 0.05 C to a battery voltage of 5.2 V in a room temperature environment, then left for 20 minutes, and CC-discharged at a constant current of 0.05 C to a battery voltage of 2.5 V, and the discharge capacity was measured.

[0043] <Examples 2 to 10 and Comparative Examples 1 to 5> In the synthesis of the lithium transition metal composite oxide, the mixing ratio and mixing conditions of LiF and LiMnO2 were changed so as to obtain the composition and lattice constant a shown in Table 1. Except for this, a test cell was prepared in the same manner as in Example 1, and the initial discharge capacity was evaluated.

[0044] [Table 1]

[0045] As shown in Table 1, all of the test cells of the examples had higher initial discharge capacities than the test cells of the comparative examples, and it can be seen that the positive electrode active materials of the examples have high capacity. When no F was contained (Comparative Example 1) and when the content of F was too high, specifically, when the composition ratio of oxygen was less than 1.3 and N F / N O When the lattice constant a of the positive electrode active material is larger than 0.6 (Comparative Examples 2 to 5), the initial discharge capacity is low and is significantly different from that of the Examples. In particular, when the lattice constant a of the positive electrode active material is smaller than 4.09 (Comparative Example 6), the discharge capacity is significantly reduced. Also, when the lattice constant a of the positive electrode active material of the comparative example is larger than 4.16 (Comparative Example 2) in the same composition, the discharge capacity is confirmed to be significantly reduced.

[0046] As described above, the positive electrode active material of the embodiment can realize a significant increase in the capacity of the battery. In addition, when the lattice constant a of the positive electrode active material is in the range of 4.09 to 4.16, particularly in the range of 4.110 to 4.135, it was confirmed that the discharge capacity tends to be high. For example, in Examples 5 and 6 using positive electrode active materials having the same composition, the active material of Example 5, which has a lattice constant a of 4.133(3), had a higher capacity than the active material of Example 6, which has a lattice constant a of 4.158(2). Thus, the lattice constant a is an important factor that greatly affects the capacity of the positive electrode active material. [Explanation of symbols]

[0047] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket

Claims

1. It has a crystal structure belonging to the space group Fm-3m, Composition formula Li x Mn y M a O b F c (wherein M is at least one metal element other than Mn, and x+y+a=b+c=2, 1<x≦1.35, 0.4≦y≦0.9, 0≦a≦0.2, 1.3≦b≦1.8), The positive electrode active material for a non-aqueous electrolyte secondary battery has a lattice constant a of 4.09 to 4.

16.

2. Composition formula Li x Mn y M a O b F c 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the Li composition ratio x satisfies 1.1≦x≦1.

3.

3. Composition formula Li x Mn y M a O b F c 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the metal element M is at least one selected from the group consisting of Ni, Sn, Mo, Ti and W.

4. 4. A non-aqueous electrolyte secondary battery comprising: a positive electrode containing the positive electrode active material according to claim 1; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Formation of coated film

    JP1986097029A

  • Cathode active material, and battery

    JP2019029343A

  • Positive electrode active material and battery

    WO2018198410A1